Tantangan Penegakan Kode Etik Penyelenggara Pemilu Oleh Dewan Kehormatan Penyelenggara Pemilu (DKPP): Analisis Perspektif Undang-Undang No. 7 Tahun 2017 Tentang Pemilihan Umum - Anam, Khoirul (Journal of Contemporary Law Studies, 2024)
The study examines the challenges and potential solutions regarding the enforcement of ethical codes by the Election Organizers Honor Council (DKPP) under the 2017 General Election Law. Established in 2012, DKPP plays a crucial role in addressing violations of election organizers' ethical codes, as evidenced by a significant volume of complaints received between June 2019 and February 2023. Its institutionalization alongside the Election Commission (KPU) and the Election Supervisory Board (BAWASLU) reflects the government's commitment to upholding ethical conduct in elections, as mandated by the 2011 Election Organizer Law. Utilizing a normative legal research method, this study delves into the legal framework provided by the 2017 General Election Law and its subsidiary regulations to analyze DKPP's effectiveness in enforcing ethical codes. Despite DKPP's interventions, such as written warnings and temporary suspensions, which have influenced the behavior of election organizers, logistical challenges persist due to Indonesia's geographical diversity. Moreover, the limited scope of sanctions poses a deterrent challenge. To enhance DKPP's effectiveness, there is a need to bolster its regional presence, ideally establishing branches in each province. This decentralized approach would improve DKPP's efficiency and accessibility, thereby reinforcing its role in safeguarding the integrity of electoral processes. Overall, while DKPP has made significant progress in enforcing ethical codes, addressing logistical constraints and expanding punitive measures are essential for further enhancing its effectiveness.